A new method for the synthesis of 4-aminobenzoic acid – an intermediate for the production of procaine - A. H. Halstian; O. P. Baula; H. V. Tarasenko (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki)
Procaine is one of the oldest local anesthetics used in medicine. When absorbed and entering the systemic circulation reduces the excitability of peripheral cholinoreactive systems. Has a blocking effect on the autonomic ganglia, reduces smooth muscle spasms, and reduces the excitability of the myocardium and motor areas of the cerebral cortex. It is synthesized by oxidizing 4-nitrotoluene to 4-nitrobenzoic acid, which is subsequently reacted with thionyl chloride, the resulting acid chloride is then esterified with 2-diethylaminoethanol to give nitrocaine. Finally, the nitro group is reduced by hydrogenation over a Raney nickel catalyst. The oxidation stage is characterized by the formation of toxic, difficult to dispose of wastewater, valuable mineral oxidants, or high temperatures and excess pressure, in the case of using oxygen as an oxidant. Therefore, the search for new environmentally friendly and low-temperature methods of obtaining 4-nitrobenzoic acid is an urgent task.